Unexpected death due to a biventricular thrombosis: Case report and review of literature. (March 2021) - Barranco, Rosario; Caputo, Fiorella; Gaggero, Gabriele; Ventura, Francesco
Cardiac thrombosis is an unusual condition characterised by the formation of a clot in the heart chambers. Biventricular thrombosis with obstruction of blood flow and fatal cardiogenic shock is anecdotal. This report describes a rare biventricular thrombosis in an elderly woman without known risk factors which was diagnosed at autopsy. A complete autopsy is essential to ascertain the cause of death, especially in complex cases with little medical history. We suggest a possible explanation for the pathophysiological mechanism.